PARP-1 Expression is Increased in Colon Adenoma and Carcinoma and Correlates with OGG1 - Dziaman, Tomasz (Public Library of Science, 2014)
The ethiology of colon cancer is largely dependent on inflammation driven oxidative stress. The analysis of 8-oxodeoxyguanosine (8-oxodGuo) level in leukocyte DNA of healthy controls (138 individuals), patients with benign adenomas (AD, 137 individuals) and with malignant carcinomas (CRC, 169 individuals) revealed a significant increase in the level of 8-oxodGuo in leukocyte DNA of AD and CRC patients in comparison to controls. The counteracting mechanism is base excision repair, in which OGG1 and PARP-1 play a key role. We investigated the level of PARP-1 and OGG1 mRNA and protein in diseased and marginal, normal tissues taken from AD and CRC patients and in leukocytes taken from the patients as well as from healthy subjects. In colon tumors the PARP-1 mRNA level was higher than in unaffected colon tissue and in polyp tissues. A high positive correlation was found between PARP-1 and OGG1 mRNA levels in all investigated tissues. This suggests reciprocal influence of PARP-1 and OGG1 on their expression and stability, and may contribute to progression of colon cancer. PARP-1 and OGG1 proteins level was several fold higher in polyps and CRC in comparison to normal colon tissues. Individuals bearing the Cys326Cys genotype of OGG1 were characterized by higher PARP-1 protein level in diseased tissues than the Ser326Cys and Ser326Ser genotypes. Aforementioned result may suggest that the diseased cells with polymorphic OGG1 recruit more PARP protein, which is necessary to remove 8-oxodGuo. Thus, patients with decreased activity of OGG1/polymorphism of the OGG1 gene and higher 8-oxodGuo level may be more susceptible to treatment with PARP-1 inhibitors.